2004
DOI: 10.1145/1035575.1035578
|View full text |Cite
|
Sign up to set email alerts
|

A study of web usability for older adults seeking online health resources

Abstract: The Web offers older adult users immediate access to health resources that might not otherwise be available. Older adult users, however, may encounter Web barriers associated with normal aging and lower education. The National Institute on Aging Web guidelines were used to assess the usability of 125 Web sites offering health resources. Performance, translation, and reading complexity were also assessed. Results showed that many of the sampled sites were not senior-friendly. Only 12% of the sites offered a Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
15

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(160 citation statements)
references
References 12 publications
4
141
0
15
Order By: Relevance
“…The latest fad is always brought to appointments.^-Diabetes Dietician Furthermore, because of the amount of data associated with the conditions, our participants suggested that it is possible that patients can get overwhelmed with the amount of medical information available to them and they may not understand the medical language. Becker (2004) concluded that many online health resources would require a college education to understand the medical information. This was similarly noted by one clinician who discussed an online health management system aimed to educate and inform patients, which ultimately failed because of the overwhelming amount of information on the site.…”
Section: Medical Information Sources Are Not Adequate For Validating mentioning
confidence: 99%
“…The latest fad is always brought to appointments.^-Diabetes Dietician Furthermore, because of the amount of data associated with the conditions, our participants suggested that it is possible that patients can get overwhelmed with the amount of medical information available to them and they may not understand the medical language. Becker (2004) concluded that many online health resources would require a college education to understand the medical information. This was similarly noted by one clinician who discussed an online health management system aimed to educate and inform patients, which ultimately failed because of the overwhelming amount of information on the site.…”
Section: Medical Information Sources Are Not Adequate For Validating mentioning
confidence: 99%
“…Utilizando as recomendações geradas pelo NIA, Becker [22] realizou um estudo de usabilidade por meio da avaliação de 125 sites web com conteúdos sobre saúde. A autora concluiu que a maioria dos sites avaliados não é amigável para o público da terceira idade, apontando como os maiores problemas encontrados: a falta de tratamento do tamanho das letras, a necessidade de destreza com o mouse para utilização dos menus de opções e a ausência de páginas de ajuda e mapas do conteúdo.…”
Section: Usabilidade Para a Terceira Idadeunclassified
“…For example, Becker reported that the majority of health Web sites are not well designed for the elderly [21], while Stossel et al found that health education material on the Web is not written at an adequate reading level [18]. Zheng and Yu have reported on the readability of electronic health records compared to Wikipedia pages related to diabetes and found that readability measures often do not align with user ratings of readability [22].…”
Section: Related Workmentioning
confidence: 99%
“…These measures generally rely on surface-level characteristics of text, such as characters, syllables and word counts (missing citation). While these measures have been widely used in studies investigating the understandability of health content retrieved by search engines (e.g., [4,5,6,7,8,9,18,21]), our preliminary work found that these measures are heavily affected by the methods used to extract text from the HTML source [13]. We were able to identify specific settings of an HTML preprocessing pipeline that provided consistent estimates, but due to the lack of human assessments, we were not able to investigate how well each HTML preprocessing pipeline correlated with human assessments.…”
Section: Related Workmentioning
confidence: 99%